The meaning of co‐production for clinicians: An exploratory case study of Practitioner Trainers in one Recovery College. Issue 5 (19th July 2018) - Dalgarno, Mark; Oates, Jennifer
Accessible summary?: What is known on the subject: Analysis of co‐production in mental health and specifically Recovery Colleges has not previously considered the impact on clinicians and their clinical practice. Co‐production as a concept is open to multiple interpretations. Core components of co‐produced work are as follows: a focus on assets, mutuality, peer support and the use of a facilitative approach. What this paper adds to existing knowledge?: Senior clinicians who have chosen to become Practitioner Trainers describe the experience of collaboration with service users in an educational rather than clinical context. Working together in this educational environment led to some shifts in their perceptions of professional power and authority, in some cases leading to personal disclosures about their mental health. This study suggests the mechanisms by which co‐production may transform professional practice: being in an educational rather than clinical context, the experience of being supported, the challenge of negotiating multiple roles (including that of being a colleague to someone with mental health needs) and experiencing a gradual shift of role emphasis as co‐trainer relationships develop. The practical challenge of holding a simultaneous role as clinician for and co‐trainer with Peer Trainers has been articulated, with the caveat that mental health support may be a feature of collegiate as well as clinical roles. What are the implications for practice?: Being a Practitioner Trainer could be a professionally transformative experience. Ground rules for how to support colleagues' mental health needs should be established and refined during co‐produced working. Negotiating personal disclosure and professional role identity must be explored further in both co‐production research and practice. Abstract: Introduction: Co‐production between service users and clinicians is a desirable element of recovery‐oriented practice in mental health, but the effect of co‐production on clinicians has not been explored thoroughly. Aim: To explore the meaning of co‐production for clinicians based on their experience of co‐production in a Recovery College. Method: Thematic analysis of eight semi‐structured interviews with clinicians who have co‐produced and co‐delivered workshops with a Recovery College Peer Trainer. Results: The "meaning of co‐production" had four themes: definitions, power dynamics, negotiating roles and influence on practice. Clinicians' experience of co‐production meant a reassessment of their expert role and power. They said that this altered their clinical practice, particularly the language they used and the personal information they shared. Discussion: Role negotiation between Practitioner and Peer Trainers is an iterative process, whereby clinicians may revise their perspectives on personal disclosure, professional identity and collegiate support. The Peer and Practitioner Trainer relationship is characterized by reciprocity and mutuality, and there is some evidence that Practitioner involvement in a co‐produced activity has the potential to transform service user and provider relationships beyond the Recovery College setting. Implications for practice: Engaging in co‐produced educational workshops can alter clinicians' perspectives on roles, power and clinical expertise. Findings from this case study must be tested against research on other Recovery Colleges.